The Effect of E-Service Quality on E-Customer Loyalty with E Customer Satisfaction as a Mediation Variable Case Study on the My BCA Mobile Banking Application - Irvandeo Wandinata Sembiring; Dedi Iskamto (Green Publisher Indonesia, 2025)
Nowadays, as competition between banks intensifies, they must provide the best service to each client in order to grow and strengthen their competitive advantage. This research investigates the impact of e-service quality on e-customer loyalty, with e-customer satisfaction as a mediating variable, specifically focusing on the My BCA Mobile Banking Application. The study aims to analyze how various dimensions of e-service quality—such as site organization, reliability, responsiveness, user-friendliness, personal needs, and efficiency—affect customer satisfaction and loyalty. The study uses a quantitative research method, with data collected from 385 active users of the My BCA mobile banking application in Indonesia. The findings reveal that e-service quality significantly influences e-customer satisfaction, which in turn positively impacts e-customer loyalty. Among the six dimensions of e-service quality, site organization, user-friendliness, personal needs, and efficiency show significant effects on both customer satisfaction and loyalty. The study emphasizes the importance of enhancing service quality to improve customer experience and foster loyalty in the competitive banking sector.